Study on Frequency Control Based on WTTP Frequency Detection Method - Zhanfeng Ying; Yunyun Chen; Junji Wu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
For improving the precision of power system frequency control under the condition of noise and harmonic interference, a new power system frequency control algorithm is proposed based on WTTP frequency detection method, which is a combination of wavelet transform and three-point frequency detection method. Fundamental component can be extracted from distorted signal by wavelet transform under asynchronous sampling, and then three-point frequency detection method is used to detect fundamental component frequency. For improving the detection precision, error mathematics mechanism of three-point frequency detection method is analyzed and error mitigation method is proposed. Even though there is noise and harmonic interference in feedback loop, power system frequency can be controlled accurately and stably by applying WTTP frequency detection method to power system frequency control. Simulation results demonstrate the feasibility of algorithm. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2665